Broadband absorber with dispersive metamaterials - Han WonHeum; Park Q-Han (Nanophotonics)
A broadband absorber that utilizes a dispersive metamaterial and covers the entire microwave X-band (8–12 GHz) is proposed in the present study. An ideal absorber attached to the surface of a perfect electric conductor requires the permittivity of the absorbing layer to be anomalously dispersive in the targeted broad frequency band. We show that anomalous dispersion of the permittivity for the X-band can be fitted to a two-pole Lorentz oscillator model and realized with the use of a double-layered, square-loop metamaterial. We explain the connection between the two-pole oscillator model and the double-layered, square-loop metamaterial using an equivalent circuit model and present explicit design rules for the metamaterial. We fabricate a 4-mm-thick metamaterial absorber with flexible silicon rubber, a resistor element, and conductive wire using carbon and silver conductive ink. Our metamaterial absorber achieves a reflectance of less than −20 dB over the entire X-band region.